Analisis Prosedur Bimbingan Karier dan Soft Skill terhadap Kompetensi Karier Mahasiswa - Dyah Ayu Pradnya Paramitha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The goal of this research was to know analysis between career guidance procedures and soft skills on the career competencies of Batam Tourism Polytechnic student. This research used a quantitative descriptive research design with two way anova methods. Population in this research of was students seventh semester students of the Study Program of Culinary Management, Room Division Management, and Food and Beverage Management at Batam Tourism Polytechnic was 104 respondents. Sample in this research was 84 respondents that determined by using proportional random sampling technique. Data collection techniques using questions. The research shows that there was significant differences between career guidance procedures to the student career competences, significant differences between soft skills to the student career competencies, and significant interaction between the implementation of career guidance to the soft skills in determining student career competencies.